Problems of Constructing Intelligent Systems. Knowledge Representation - Meytus, V. Yu (Cybernetics and systems analysis, 2019)
This article considers the construction of a formal model of a subject area for an intelligent system using intelligence with descriptive logic. Three interrelated category models are created. In particular, the representation of knowledge about a subject area is defined as a category of knowledge. Some properties of the introduced categories and the relationship between the category of knowledge and the ability to solve problems in the subject area being modeled are considered.